Generational Needs vs. Media Selection - Kuźmicz, Krzysztof; Chmielewska, Aleksandra (Roczniki Nauk Społecznych, 2024)
In recent years, much attention in the research market has been devoted to the issue of the impact of generational needs on the choice of media by individuals. These unique socio-cultural characteristics have a major impact on the experience, information processes and media exploitation of a given population. Generational needs have the opportunity to express themselves in various forms around the world, and their influence on the choice of media consumption is undeniable and important. The article aims to gain insight into media preferences and choices among generations X, Y, Z and BB (Baby Boomers). The study was carried out in the period March–May 2023 and was based on data obtained from Mediapanel by Gemius and secondary data by KIM and Nielsen.